2017
DOI: 10.34071/jmp.2017.2.17
|View full text |Cite
|
Sign up to set email alerts
|

The Application of the New 2015 Aha Guidelines on Update for Cardiopulmonary Resuscitation and Emergency Cardiovascular Care: On Occasion of a Successful Case at Hanoi Medical University Hospital

Abstract: Cardiac arrest is associated with high mortality if without early diagnosis and cardiopulmonary resuscitation. Each minute without emergency cardiopulmonary resuscitation (CPR), the patient’s chance of survival is reduced by ten percent, even if properly resuscitated but not recirculated, the chance of survival is reduced by four percent. Therefore, CPR should be ferformed as soon as patient is diagnosed with cardiac arrest with the signs of unconsciousness, apnea, loss of carotid pulse and inguinal pulse. Che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Medical records of the group of patients with surgery duration of 120 minutes or less with prophylactic antibiotics treatment in compliance with the rules were 2.784 times higher than those with surgery duration above 120 minutes. Research by Huong showed that there was no relationship between the surgery duration and the use of prophylactic antibiotics, P > .05; it could be explained by the fact that there is various type of diseases in our research while Huong 7 only studied on 1 disease (laparoscopic cholecystectomy) so this difference is explainable. Hospital stays with prophylactic antibiotics treatment complying with the regimen: patients with stays of less than 5 days with prophylactic antibiotics treatment in compliance with the rules accounted for 55.2%, lower than those with 5 or more days of hospital stays (57.7%).…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…Medical records of the group of patients with surgery duration of 120 minutes or less with prophylactic antibiotics treatment in compliance with the rules were 2.784 times higher than those with surgery duration above 120 minutes. Research by Huong showed that there was no relationship between the surgery duration and the use of prophylactic antibiotics, P > .05; it could be explained by the fact that there is various type of diseases in our research while Huong 7 only studied on 1 disease (laparoscopic cholecystectomy) so this difference is explainable. Hospital stays with prophylactic antibiotics treatment complying with the regimen: patients with stays of less than 5 days with prophylactic antibiotics treatment in compliance with the rules accounted for 55.2%, lower than those with 5 or more days of hospital stays (57.7%).…”
Section: Discussionmentioning
confidence: 56%
“…Table 2 shows that, the proportion of medical records of patients who have used antibiotics before hospitalization is 5.4% (39/724). Huong 7 stated that 21.6% of patients used antibiotics before being hospitalized for endoscopic cholecystectomy at Hanoi Medical University hospital. In case of the use of antibiotics before surgery, the surgeons often consider before deciding whether or not to use prophylactic antibiotics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation